STRATEGY OF EXHAUST MUNICIPAL WASTE LANDFILL RECULTIVATION - Pavliukh, Lesia; Syrotina, Iryna; Todorovych, Olena (Proceedings of National Aviation University (archive), 2020)
Purpose and Objectives of the Work. This scientific paper is devoted to waste treatment issues. The aim of this scientific investigation ison the basis of prototype analysis to develop a modern waste management technology, which includes proposals for further exploitation the territory of exhaust Stadnytske landfill. Methods of Research: the statistical and theoretical methods, analysis, comparison. Research Results. Neutralization the negative impact on the environment of the landfill, in the way of conversion the landfill into the poplars forest; recreation zone creation on the former landfill; creation of the complex recycling enterprises; formation of the bio-polygon for the production of the natural fertilizers; installation of the biogas reactors for methane production; decrease contamination by waste water; reforestation of the territory; gaining the economic benefits by the way second raw material usage. Discussion. Іmplementation of this complex for prevention danger for people, first of all. The complex waste treatment technology includes successive steps that take into account the ecological, economic and social spheres of life. After analysis of economic efficiency of the cement blocks system and the biogas reactors, we can recommend both for generating income from garbage disposal.